Association between Micronutrient Levels and Chronic Spontaneous Urticaria. (22nd October 2015) - Wu, Cheng-Han; Eren, Efrem; Ardern-Jones, Michael Roger; Venter, Carina
Abstract : Previous reports have suggested a possible role for vitamin D in the etiology of chronic spontaneous urticaria (CSU); however, little information is available regarding the role of other micronutrients. We, therefore, analyzed vitamin D, vitamin B12, and ferritin levels in CSU patients (n = 282 ) from a preexisting database at Southampton General Hospital. Data were compared against mean micronutrient levels of the general population of the UK, obtained from the National Diet and Nutrition Survey. Vitamin D levels of CSU patients were found to be higher than those of the general UK population (P = 0.001 ). B12 levels were lower in patients with CSU (P < 0.001 ) than in the general population. Ferritin levels were found to be lower in male CSU patients than in the general male population (P = 0.009 ). This association between low B12 and iron levels and CSU might indicate a causal link, with micronutrient replacement as a potential therapeutic option.